Bond graph modeling, design and experimental validation of a photovoltaic/fuel cell/ electrolyzer/battery hybrid power system. (9th July 2021) - Badoud, Abd Essalam; Merahi, Farid; Ould Bouamama, Belkacem; Mekhilef, Saad
Abstract: This work presents a complete bond graph modeling of a hybrid photovoltaic-fuel cell-electrolyzer-battery system. These are multi-physics models that will take into account the influence of temperature on the electrochemical parameters. A bond graph modeling of the electrical dynamics of each source will be introduced. The bond graph models were developed to highlight the multi-physics aspect describing the interaction between hydraulic, thermal, electrochemical, thermodynamic, and electrical fields. This will involve using the most generic modeling approach possible for managing the energy flows of the system while taking into account the viability of the system. Another point treated in this work is to propose. In this work, a new strategy for the power flow management of the studied system has been proposed. This strategy aims to improve the overall efficiency of the studied system by optimizing the decisions made when starting and stopping the fuel cell and the electrolyzer. It was verified that the simulation results of the proposed system, when compared to simulation results presented in the literature, that the hydrogen demand is increased by an average of 8%. The developed management algorithm allows reducing the fuel cell degradation by 87% and the electrolyzer degradation by 65%. As for the operating time of the electrolyzer, an increment of 65% was achieved, thus improving the quality of the produced hydrogen. The Fuel Cell's running time has been decreased by 59%. With the ambition to validate the models proposed and the associated commands, the development of this study gave rise to the creation of an experimental platform. Using this high-performance experimental platform, experimental tests were carried out and the results obtained are compared with those obtained by simulation under the same metrological conditions. Highlights: Bond Graph for hydrogen-related renewable energy systems. A green-green energy system combining PV, fuel cell, electrolyzer, and the battery is proposed. Power modeling and energy management using Bond graph. The control of power flow from sources and to/from storage devices is developed. Experimental results investigation of hydrogen-related renewable energy systems.